2018
DOI: 10.1111/ecog.03795
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between facilitation and habitat type drives spatial vegetation patterns in global drylands

Abstract: The spatial configuration of vascular vegetation has been linked to variations in land degradation and ecosystem functioning in drylands. However, most studies on spatial patterns conducted to date have focused on a single or a few study sites within a particular region, specific vegetation types, or in landscapes characterized by a certain type of spatial patterns. Therefore, little is known on the general typology and distribution of plant spatial patterns in drylands worldwide, and on the relative importanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 88 publications
(188 reference statements)
2
34
0
1
Order By: Relevance
“…Compared to other shrub species, L. tridentata can be a poor facilitator (Hutto, McAuliffe, & Hogan, 1986; reviewed by Callaway, 2007) due to relatively strong competitive effects and allelopathy (Mahall & Callaway, 1992 dant in the open as aridity increased, but it is unclear which occurred (Table A5; note the lack of a significant microsite × aridity interaction). The former could occur if the quantity, quality or availability of soil resources concentrated under L. tridentata canopies (Schlesinger, Raikes, Hartley, & Cross, 1996) Michalet & Pugnaire, 2016), and can be influenced by the spatial structure of vegetation (Berdugo, Soliveres, Kéfi, & Maestre, 2019 (Schlesinger et al, 1996).…”
Section: Ta B L Ementioning
confidence: 99%
“…Compared to other shrub species, L. tridentata can be a poor facilitator (Hutto, McAuliffe, & Hogan, 1986; reviewed by Callaway, 2007) due to relatively strong competitive effects and allelopathy (Mahall & Callaway, 1992 dant in the open as aridity increased, but it is unclear which occurred (Table A5; note the lack of a significant microsite × aridity interaction). The former could occur if the quantity, quality or availability of soil resources concentrated under L. tridentata canopies (Schlesinger, Raikes, Hartley, & Cross, 1996) Michalet & Pugnaire, 2016), and can be influenced by the spatial structure of vegetation (Berdugo, Soliveres, Kéfi, & Maestre, 2019 (Schlesinger et al, 1996).…”
Section: Ta B L Ementioning
confidence: 99%
“…In addition, and within similar aridity gradients such as those we investigated, other studies carried out in drylands have found nonlinear changes in significant ecological properties and mechanisms. These include drastic declines in ecosystem functioning accompanied by abrupt changes of vegetation spatial patterns from power law like to nonpower law like (Berdugo, Kéfi, et al, ; Berdugo, Soliveres, Kéfi, & Maestre, ); shifts in the mechanisms driving the structure of plant communities from facilitation driven to competition driven (Berdugo, Maestre, et al, ); the decoupling of soil carbon, nitrogen, and phosphorus cycles (Delgado‐Baquerizo et al, ); and changes in nitrogen turnover rates (Wang et al, ). Therefore, we hypothesize that at aridity levels around 0.7–0.8, many structural changes occurring on the ecosystem may influence each other through these interacting feedbacks.…”
Section: Discussionmentioning
confidence: 99%
“…Transitions between different ecological states, e.g. vegetated towards bare soil, can be sometimes observed in the same landscape under the presence of environmental gradients [ 31 ]. In this context, it has been conjectured that spatial correlations can be used as indicators of forthcoming green-desert shifts [ 15 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%